Avid Liquid 7 for Windows - Ekert, Paul (Avid Liquid Seven for Windows Berkeley, CA : USA, 2006)
Digital video--Editing.\Pinnacle liquid edition.
Age Group: Adult
... the previous edition of this book, Pinnacle Liquid Edition 6 ...
Keywords: Paul Ekert ; [editor, Karyn Johnson]